2017
DOI: 10.1186/s12885-017-3215-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of transforming growth factor-beta in patients with colorectal cancer who undergo surgery: a meta-analysis

Abstract: BackgroundTransforming growth factor-beta (TGF-β) is associated with a higher incidence of distant metastasis and decreased survival. Whether TGF-β can be used as a prognostic indicator of colorectal cancer (CRC) remains controversial.MethodsThe Medline, EMBASE and Cochrane databases were searched from their inception to March 2016. The studies that focused on TGF-β as a prognostic factor in patients with CRC were included in this analysis. Overall survival (OS) and disease-free survival (DFS) were analysed se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…The correlation of immunohistochemical expression with the clinicopathological parameters associated with CRC revealed that high TGF-β expression and low TGF-βR1, TGF-βR2, Smad4, pSmad2/3, and E-cadherin expression were correlated with the tumor–node–metastasis (TNM) stage of the disease [ 34 ]. Finally, the meta-analysis by Chen XL and colleagues in 2017 showed that TGF-β tissue expression can be used as a prognostic biomarker for CRC patients undergoing surgery, especially for CRC patients from Western countries [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The correlation of immunohistochemical expression with the clinicopathological parameters associated with CRC revealed that high TGF-β expression and low TGF-βR1, TGF-βR2, Smad4, pSmad2/3, and E-cadherin expression were correlated with the tumor–node–metastasis (TNM) stage of the disease [ 34 ]. Finally, the meta-analysis by Chen XL and colleagues in 2017 showed that TGF-β tissue expression can be used as a prognostic biomarker for CRC patients undergoing surgery, especially for CRC patients from Western countries [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor tissues express higher levels of TGF-β and these levels can be correlated with patient survival (185)(186)(187). Upregulation of TGF-β expression was also observed in glioma models resistant to anti-VEGF therapy (188).…”
Section: Transforming Growth Factor-β Role Of Transforming Growth Facmentioning
confidence: 99%
“…In Chen et al (2017) carried out a meta-analysis and found out that up-regulated TGF-β had a favorable impact on overall survival (OS) and disease-free survival (DFS) in CC patients and might be used as a prognostic biomarker for CC patients undergoing surgery. Later, Zessner-Spitzenberg et al (2019) also concluded that elevated levels of TGFβ served as a poor prognostic biomarker of CC.…”
Section: Discussionmentioning
confidence: 99%